Culture de l’impolitesse, célébrités politiques et médias socionumériques - Olivier Turbide (Communication)
This article considers the way (T.V.) audiences react to aggressive behaviour during a “confrontainment”-style political interview. Comparing reviews of the same interview by a live studio audience and by T.V. audiences commenting on Twitter, this study of a Québec talk show explores the buy-in and opt-out dynamics that play out in response to aggressive behaviour and the person exhibiting it, within specific viewing frames. The results show that the T.V. audience had a higher tolerance for aggressive behaviour than the live studio audience, inciting the interviewer to be more aggressive toward the politician being interviewed.